PERAN PEMERINTAH DESA DUNGUN DALAM MEWUJUDKAN PERLINDUNGAN ANAK DARI KEKERASAN PADA KASUS ANAK-ANAK BERMAIN LAYANG-LAYANG DI AREA PERSAWAHAN - Alif Naufal Syarifudin; Rahmanu Wijaya (Triwikrama: Jurnal Ilmu Sosial, 2025)
Child protection from violence is a critical issue requiring attention from all levels of government, including village administrations. Children have fundamental rights that must be guaranteed, such as the right to live, grow, and develop in a safe environment. However, in Dungun Village, Tongas Subdistrict, Probolinggo Regency, cases of violence against children, both physical and verbal, frequently occur, particularly in the context of conflicts between children and farmers due to playing activities in agricultural fields. This study aims to analyze the role of the Dungun Village administration in realizing children's right to protection from violence as stipulated in Article 1 Paragraph 15a of Law No. 35 of 2014, focusing on providing a safe environment for children to play. Additionally, the study seeks to identify the obstacles faced by the village administration in exercising its authority, including conflicts arising from traditional games in agricultural areas. This research uses a descriptive qualitative method with a case study approach. Data collection techniques include interviews, observations, and documentation involving the village head, village officials, farmers, children, and local community members directly involved in related violence or conflicts. The findings indicate that the village administration plays a significant role in supporting child protection but faces challenges such as the absence of specific regulations for children, societal perceptions of violence as a form of discipline, and limited resources. The conflict between farmers and children playing in agricultural fields poses its own challenges, although police intervention in 2022 successfully reduced such incidents. This study concludes that the village administration's role must be strengthened through clearer regulations, public awareness campaigns on children's rights, and the provision of safe play areas for children. Collaboration with the community and authorities is key to overcoming obstacles and creating a child-friendly environment.